Peak hip external rotation torque and single-rater reliability is influenced by measurement position in the ISOMED2000 - Frese, C.; Siebert, T-: Bubeck, D.; Astner, I.; Sitte, D.; Alt, W. (Sports Biomechanics, 2025)
Measurement of hip external rotation strength (ERS) is important for preventive and rehabilitative purposes. ERS can be measured in 3 different positions in the isokinetic dynamometer ISOMED2000. However, it is not clear whether these measurement positions effect ERS nor if these positions are reliable in the ISOMED2000. Hence, the purpose of this study was to compare ERS in these positions, the reliability and the agreement. A cross-sectional design was conducted to compare measurement positions and a test-retest design to assess intra-rater reliability and agreement. Twenty-four healthy, physically active athletes participated in the study. Peak isometric torque was measured in the ISOMED in prone, supine, and side-lying position across two sessions on one day. Differences between positions were evaluated with the Wilcoxon-signed-rank test and cliff`s delta. Reliability was assessed via intraclass correlation. Agreement was determined using the standard error of measurement (SEM), minimal detectable change (MDC), and Bland-Altman analysis (BAA). Results indicated a significant influence of measurement position on ERS (p < 0.001) with high effect sizes (>0.74). Reliability and agreement were high in all positions, but highest for the side-lying position (ICC = 0.90 [0.78, 0.96]; SEM = 0.08; MDC = 0.23; BAA_bias = 3.4 %, BAA_loA = 37 %). There were only poor to moderate correlations between measurement positions. These findings suggest that measurement position significantly affects ERS. Furthermore, the effect varies across individuals indicating that normative values cannot be used interchangeably or be adapted across positions. In diagnostic testing ERS should be measured in the same position, but preferably in the side-lying position.